2015
DOI: 10.1038/srep11988
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Host-Microbiome Interactions using an in Silico Model of Biomimetic Robots and Engineered Living Cells

Abstract: The microbiome’s underlying dynamics play an important role in regulating the behavior and health of its host. In order to explore the details of these interactions, we created an in silico model of a living microbiome, engineered with synthetic biology, that interfaces with a biomimetic, robotic host. By analytically modeling and computationally simulating engineered gene networks in these commensal communities, we reproduced complex behaviors in the host. We observed that robot movements depended upon progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…Therefore, further studies should be conducted to assess whether the anticancer potential is mainly due to the gastrointestinal lysate or the secretions from the gut microbiota. Since the gut microbiota is known to be beneficial to its host (Heyde and Ruder, 2015;Louis et al, 2014;Kang et al, 2017;Kelly et al, 2017;Zhou et al, 2017). Moreover, studies have shown that the metabolites synthesized by the gut microbiota are transported to the brain through the blood (Belkaid and Hand, 2014;Clos-Garcia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies should be conducted to assess whether the anticancer potential is mainly due to the gastrointestinal lysate or the secretions from the gut microbiota. Since the gut microbiota is known to be beneficial to its host (Heyde and Ruder, 2015;Louis et al, 2014;Kang et al, 2017;Kelly et al, 2017;Zhou et al, 2017). Moreover, studies have shown that the metabolites synthesized by the gut microbiota are transported to the brain through the blood (Belkaid and Hand, 2014;Clos-Garcia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from using genetic toggle switches in microrobots, macroscale robots can adopt synthetic biology tools as their perception-action loop modules. Heyde and Ruder proposed using engineered bacteria equipped with genetic toggle switches to maneuver a biomimetic, macroscale robot 12 [ Fig. 8(c) ].…”
Section: Synthetic Biology and Roboticsmentioning
confidence: 99%
“…For example, Heyde and Ruder showed using the engineered microbiome in microbiome–host interactions to affect host behaviors. 12 In a bio-inspired swimming robot ray developed by Park and co-workers, cardiomyocytes powered the actuation and served as a perception-action module. 13 The way batoid fish swim is highly energy-efficient, which is a desirable trait in robotic systems.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiome is well recognized to have a pivotal role in the regulation of the health and behaviour of its’ host (Heyde and Ruder 2015). Recently, there has been a plethora of studies on the human microbiome.…”
Section: Introductionmentioning
confidence: 99%